KAJIAN ALGORITMA CRAIG RAYNOLD PADA KERUMUNAN (FLOCKING) - Ginting, Lit Malem; Siahaan, Binsar; Situmorang, Bastian; Manik, Riris (Journal Information System Development (ISD), 2018)
Artificial Intelligence (AI) is a study of making computers that do things that today can be done better by humans. One application in the game is to mimic the behavior of animals in the wild. Set of animal in the wild are often called crowds, herds, schools and swarms. Crowds are animals that gather together in an irregular and unfocused way [4]. In 1987, Craig Reynolds [6] with his book "Flock, Herd, Schools: A Distributed Behavioral Model" invented a technique for simulating animal crowds in the wild. The technique is called flocking which is commonly known as "boids". In this study, an observation about the comparison of boids with the amount of resources used in a simulation game that will be given a device. The number of boid that will be used is 1-500 boid with cohession radius distance = 10 and 15, radius separator = 4 and save radius = 6 with the observation at the angle of 300 and 1800. Based on the results done, then the result is boids neighbor detection radius has a major effect on resource usage.Â Keywords: Artificial Intelligence (AI), Flocking, Craig Raynold, resource device